The Conquest of Mexico in the political cultures of Spanish romantic nationalism (1829-1850) - Escribano Roca, Rodrigo (Historia y Política, 2022)
The article addresses the role of the representations of the Conquest of Mexico in the processes of nationalization orchestrated by the political cultures of post-revolutionary Spain. The research focuses on the period that went from the definitive failure of the attempts to reconquer the old Viceroyalty of New Spain until the middle of the century, thus coinciding with the rise of romantic historicism in Spain. In the first place, and starting from a constructivist paradigm, the paper examines the consensual narratives constructed by liberal historiography and their placement at the service of a Hispanic myth that constructed a heroic image of the conquerors, characterizing them as a model of virility associated with national greatness and imperial regeneration. In the second place, using the methods of nationalization studies, the paper addresses the circulation and reproduction of the mythification of the Conquest in multiple languages, communication channels and spaces for sociability —press, museums, theatrical and operatic works, public commemorations, speeches, parliamentary rhetoric— that shaped the national imaginaries of the moment in the public sphere. Finally, the postulates of the studies of political cultures will be used to understand how, on the matrix of a generally shared Hispanic imaginary, the tendencies of thought of the moment —radicals, liberal conservatives, anti—liberal sectors, republicans, and heterodox figures such as Gertrudis Gómez de Avellaneda— elaborated competing narratives about the ultimate meaning of the Conquest, in order to cement their particular ideological projects.